2010
DOI: 10.1038/sc.2010.131
|View full text |Cite
|
Sign up to set email alerts
|

Survival after short- or long-term ventilation after acute spinal cord injury: a single-centre 25-year retrospective study

Abstract: Study design: A retrospective review of acute spinal cord injury patients having assisted ventilation on or after admission between 1981 and 2005. Objective: To assess survival after acute ventilatory support. Setting: Northwest Regional Spinal Injuries Centre, Southport, England. Methods: Causes of death were ascertained from the Office of National Statistics. Kaplan-Meier analysis of survival was calculated according to ventilator-wean status at discharge. Risk factors were obtained by Cox regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…For consistency, we kept to our original study grouping (high tetra ABC, low tetra ABC, para ABC and all Ds) and just added a ventilator-dependent group, which included either full-time or part-time mechanical ventilation, as long as it was permanent, and phrenic nerve stimulators. DeVivo and Ivie, 21 Shavelle et al, 22 Watt et al 23 and Hatton et al 24 analysed ventilator-dependent cases separately. We included ventilatordependent cases in our updated sample, and this group had significantly higher mortality ORs-seven and a half times higher than the Frankel/AIS D group-and correspondingly shorter life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…For consistency, we kept to our original study grouping (high tetra ABC, low tetra ABC, para ABC and all Ds) and just added a ventilator-dependent group, which included either full-time or part-time mechanical ventilation, as long as it was permanent, and phrenic nerve stimulators. DeVivo and Ivie, 21 Shavelle et al, 22 Watt et al 23 and Hatton et al 24 analysed ventilator-dependent cases separately. We included ventilatordependent cases in our updated sample, and this group had significantly higher mortality ORs-seven and a half times higher than the Frankel/AIS D group-and correspondingly shorter life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Data from the National Spinal Cord Injury Statistical Center in the United States indicate that people with SCI who are ventilator dependent have approximately half the life expectancy of similarly injured non-ventilated individuals, and the cause of death is respiratory in over 50% of cases. [1][2][3] Reaching ventilator liberation early in the rehabilitation course not only increases life expectancy but also improves quality of life, decreases costs [3][4][5] and enhances participation in rehabilitation. There is no consensus, however, on the best method of weaning SCI patients or on the optimal tidal volume (Vt) to be used.…”
Section: Introductionmentioning
confidence: 99%
“…Serious urinary system complications, especially chronic renal failure, due to bladder dysfunction are always the leading causes of death. [1][2][3][4] A survey study performed in 2004 showed that patients rated restoration of bladder function as important, which was ranked second after sexual function in paraplegic patients, and third after hand and sexual function in quadriplegic patients. 5 During the past century, many studies have focused on treatments to regain function in a decentralized bladder after SCI or spinal root injury; these treatments have included bladder reinnervation, sacral root electrostimulation, highly selective rhizotomy of sacral roots, direct reinnervation of the detrusor muscle, intermittent catheterization and creation of an artificial reflex pathway.…”
Section: Introductionmentioning
confidence: 99%